PENERAPAN METODE MARKET DAY UNTUK MENINGKATKAN KEMAMPUAN LITERASI NUMERASI SISWA SEKOLAH DASAR - Muhammad Samsul Aditiya; Nur Wiji Sholikin (IEC: Journal of Educational Innovation, 2025)
Numeracy literacy is a fundamental skill that elementary school students must acquire to understand and apply mathematical concepts in everyday life. However, numeracy learning in elementary schools is still predominantly abstract, causing students’ numeracy literacy to be underdeveloped. This study aims to describe the implementation of the Market Day method in improving elementary school students’ numeracy literacy skills. The study employed a descriptive qualitative approach with students of SDIT Permata Leces as the research subjects. Data were collected through observations, interviews, a simple numeracy literacy test, and documentation. The research was conducted in October 2025. The findings indicate that the Market Day method creates contextual and meaningful numeracy learning experiences. Students actively engage in buying and selling activities that require the application of numeracy concepts such as addition, subtraction, and contextual problem solving. Moreover, students demonstrate improved numeracy understanding, learning motivation, and self-confidence in using numeracy skills. Therefore, the Market Day method can serve as an alternative learning strategy to support the enhancement of numeracy literacy in elementary schools.